Modified inverted-L glabellar flap for coverage of nasal dorsum defects: a case series - Orozco Grados, Jose de Jesus; Quijano Hernandez, Mario; Sanchez Llamas, Luis Adolfo; Avila Lopez, Sonia Yorlli; Macias Medina, Daniel; Garcia Garcia, Jose Antonio (International Journal of Research in Medical Sciences, 2024)
Nasal reconstruction, particularly of the nasal dorsum, presents significant challenges due to the intricate aesthetic subunits and complex vascular supply. Traditional techniques often face limitations in terms of coverage and aesthetic outcomes. This study aims to enhance reconstructive outcomes by employing advanced flap designs, specifically the Inverted-L and modified frontonasal or glabellar flaps, to address these limitations. This study presents a single-surgeon retrospective case series involving sixteen patients diagnosed with isolated Basal Cell Carcinoma on the nasal dorsum. Between 2019 and 2021, patients underwent wide lesion resections with clear margins, followed by flap coverage using the Inverted-L or modified frontonasal flap. The flap design was planned to avoid the supratrochlear artery and ensure optimal vascular supply. Postoperative care included the use of medical-grade silicone sheets for scar management, and patients were monitored for two years for any recurrences or complications. The patient cohort included a diverse age range with no long-term flap compromise or dehiscence reported. The mean follow-up period was 24 months (range, 6 months to 3 years). Minor complications involved the removal of absorbable internal stitches in three cases due to granuloma and pustule formation. All patients achieved satisfactory aesthetic results with no tumor recurrence or significant adverse events. This case series demonstrates the efficacy of the Inverted-L flap in nasal dorsum reconstruction, offering significant improvements in both aesthetic and functional outcomes. The technique allows for versatile flap manipulation while maintaining robust vascular support, crucial for optimal healing and minimal scar visibility.